Innovative interpretations aimed at developing the knowledge of young people of new Uzbekistan - Khoshimova Sevara Sheraliyevna (Academia One Publishing, 2023)
In the article, along with the correct orientation of young people in order to prepare competitive personnel in the conditions of the market economy, the use of innovations in the educational process, as well as the "hard" qualification ("hard" qualification, which has been given special emphasis in education "skills") are being replaced by "soft", "adaptive" qualifications ("softskills"), which are gaining priority in the process of globalization, automation, robotization, digitization, based on scientific and pedagogical reasons
Keywords: market economy; quality of specialist training; Innovation process